The use of silver solid amalgam electrodes for voltammetric and amperometric determination of nitrated polyaromatic compounds used as markers of incomplete combustion - Yosypchuk, Oksana; Karásek, Jindřich; Vyskočil, Vlastimil; Barek, Jiří; Pecková, Karolina (TheScientificWorldJournal, 2012)
Genotoxic nitrated polycyclic aromatic hydrocarbons (NPAHs) are formed during incomplete combustion processes by reaction of polycyclic aromatic hydrocarbons (PAHs) with atmospheric nitrogen oxides. 1-Nitropyrene, 2-nitrofluorene, and 3-nitrofluoranthene as the dominating substances are used as markers of NPAHs formation by these processes. In the presented study, voltammetric properties and quantification of these compounds and of 5-nitroquinoline (as a representative of environmentally important genotoxic heterocyclic compounds) have been investigated using a mercury meniscus modified silver solid amalgam electrode (m-AgSAE), which represent a nontoxic alternative to traditional mercury electrodes. Linear calibration curves over three orders of magnitude and limits of determination mostly in the 10(-7) mol L(-1) concentration range were obtained using direct current and differential pulse voltammetry. Further, satisfactory HPLC separation of studied analytes in fifteen minutes was achieved using 0.01 mol L(-1) phosphate buffer, pH 7.0 : methanol (15 : 85, v/v) mobile phase, and C(18) reversed stationary phase. Limits of detection of around 1 · 10(-5) mol L(-1) were achieved using amperometric detection at m-AgSAE in wall-jet arrangement for all studied analytes. Practical applicability of this technique was demonstrated on the determination of 1-nitropyrene, 2-nitrofluorene, 3-nitrofluoranthene, and 5-nitroquinoline in drinking water after their preliminary separation and preconcentration using solid phase extraction with the limits of detection around 1 · 10(-6) mol L(-1).
Keywords: Nitrates; elektrody; elektrochemické techniky; Polycyclic Compounds; polycyklické sloučeniny; Silver; Electrodes; stříbro; dusičnany; Electrochemical Techniques